The Relationship between Trade Openness and GDP Growth Rate: The Case of South Africa (1994Q1-2008Q4) - Mosikari, Teboho Jeremiah (Journal of Economics and Behavioral Studies, 2013)
Despite substantial economic restructuring, South Africa’s post-1994 export performance is less than what might have been expected or hoped for. The study examines the trade-openness ledgrowth hypothesis in the South African economy. Further, the study uses conventional cointegration approach called Johansen cointegration technique to determine the long-run relationship between trade openness and GDP growth. The cointegration tests show that there exists long-run relationship between trade openness and GDP growth at 1% and 5% significance level. Therefore, the study also applies an error correction model to determine the speed of adjustment and the short-term determinants of GDP growth in South Africa. In considering trade openness measures, it indicates that they are generally less pivotal and have an even smaller effect than had been anticipated. The study also adopts Granger causality tests to examine whether growth in trade openness stimulate GDP growth (or vice versa). The results suggest that in all trade openness measures that are used, there is weak evidence suggesting causality from GDP to exports or vice versa. The study recommends that openness trade policy will be beneficial strategy for South Africa in the long-run. Therefore, it is suggested that the South African government continue the policy of trade openness.